Frost in Nilgiris.: Klimatologische und ökologische Beobachtungen in den kalten Tropen Südindiens - von Lengerke, Hans J. (ERDKUNDE, 1978)
By discussing the spatial and temporal aspects of frost formation in the Nilgiris-its distribution, frequency and intensity -the author presents the first systematic investigation of frost in South India and thus fills a regional gap in our knowledge of this climatic phenomenon of the cold tropics. The analysis is based on all available, mainly unpublished and scattered information (instrumental as well as visual records) collected during field work in1972/ 73. It reveals that in the Nilgiris, particularly in the central and western parts of the elevated plateau, night frost is an annually recurrent, though highly variable, climatic feature during a potential frost season of almost six months -from the third week in October to the second week in April -with a maximum frequency in January. If surface and weather conditions are favourable to its formation, frost may occur from 1400 m above sea-level to the highest peak (Dodabetta, 2636 m) wherever topography allows the cold air near the ground to accumulate and stagnate during clear and calm nights. Frost forms a major hazard for the cultivation of both agricultural and silvicultural plants -including vegetables, potatoes or tea and eucalypts or wattles, respectively. In certain frost prone areas damage may be very sever, so that expensive frost protection methods have to be applied in order to save the crop. Frost in the Nilgiris is, therefore, not only an interesting phenomenon from the climatological point of view, but it is also a challenging geoecological problem that calls for further applied research.